Sensory nerve EP4 facilitates heterotopic ossification by regulating angiogenesis-coupled bone formation - Rongmin Lin; Hancheng Lin; Chencheng Zhu; Jieming Zeng; Jiahui Hou; Ting Xu; Yihui Tan; Xuyou Zhou; Yuan Ma; Mankai Yang; Kuanhai Wei; Bin Yu; et al. (Journal of Orthopaedic Translation)
Objective: Heterotopic ossification (HO) refers to the abnormal development of bone in soft tissue rather than within bone itself. Previous research has shown that sensory nerve prostaglandin E2 receptor 4 (EP4) signaling not only governs pain perception but also influences bone formation. However, the relationship between sensory nerve EP4 and the pathogenesis of HO in the Achilles tendon remains unclear. This study aims to investigate this relationship and the underlying mechanisms. Methods: We generated sensory nerve EP4-specific knockout mice, with the genotype of Avil-CreEP4fl/fl, was propagated. Transcriptome sequencing and bioinformatics analysis techniques were used to identify the potential molecular pathways involving with sensory nerve EP4. Additionally, a neurectomy mouse model was created by transecting the sciatic nerve transection, to examine the effects and mechanisms of peripheral innervation on HO in vivo. Micro-CT, immunofluorescence (IF), Hematoxylin and Eosin (H&E) Staining, Safranin O-Fast Green staining and western blotting were used to analyze changes in cellular and tissue components. Results: We here observed an increase in sensory nerve EP4 and H-type vessels during the pathogenesis of HO in both human subjects and mice. Proximal neurectomy through sciatic nerve transection or the targeted knockout of EP4 in sensory nerves hindered angiogenesis-dependent bone formation and the development of HO at the traumatic site of the Achilles tendon. Furthermore, we identified the Efnb2 (Ephrin-B2)/Dll4 (Delta-like ligand 4) axis as a potential downstream element influenced by sensory nerve EP4 in the regulation of HO. Notably, administration of an EP4 inhibitor demonstrated the ability to alleviate HO. Based on these findings, sensory nerve EP4 emerges as an innovative and promising approach for managing HO. Conclusion: Our findings demonstrate that the sensory nerve EP4 promotes ectopic bone formation by modulating angiogenesis-associated osteogenesis during HO. The translational potential of this article: Our results provide a mechanistic rationale for targeting sensory nerve EP4 as a promising candidate for HO therapy.